Fracture mechanics analysis of hardmetals by using artificial small-scale flaws machined at the surface through short-pulse laser ablation. (February 2023) - Ortiz-Membrado, L.; Liu, C.; Cabezas, L.; Lin, L.L.; Fooladi Mahani, S.; Wang, M.S.; Jiménez-Piqué, E.; Llanes, L.
Abstract: Laser ablation has become an innovative treatment for cemented carbides, regarding edge rounding and surface modification, aiming to improve their tribomechanical performance. Meanwhile, the precision offered for this technique has also positioned it as an effective mean to generate micronotches used for evaluation of mechanical properties in structural materials. However, similar approach has not been attempted for hardmetals; thus, it becomes the main objective of this work. Dimple-like and elongated micronotches are introduced in one fine-grained WC-11%wtCo grade. In doing so, laser processing parameters are first optimized to attain micronotches with appropriated geometry and size, i.e. similar to critical flaws identified in broken pristine specimens. Success of the implemented approach is then validated through subsequent flexural testing, fractographic inspection and fracture mechanics analysis of the results attained on samples containing surface micronotches, as far as laser-induced residual stresses are taken into consideration. In this regard, elongated micronotches are found to exhibit lower residual stresses, and postulate themselves as the optimal option of the two micronotch types studied. The suitability of laser ablation for shaping artificial small-scale flaws opens a new route for introducing controlled defects, alike those intrinsic to processing or induced during service, key aspect for further understanding damage tolerance issues in cemented carbides. Highlights: Laser ablation (LA) is a suitable route for introducing artificial small-scale flaws in cemented carbides. Small-scale micronotches, shaped by LA, is a feasible option for fracture mechanics analysis of hardmetals. Residual stresses induced by LA should be taken into consideration for reliable fracture mechanics analysis. Elongated micronotches are found to exhibit lower residual stresses, as compared to dimple-like ones.